2005
DOI: 10.1039/b507715j
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman spectroscopic identification of bacterial cells of the genus Staphylococcus and dependence on their cultivation conditions

Abstract: Microbial contamination is not only a medical problem, but also plays a large role in pharmaceutical clean room production and food processing technology. Therefore many techniques were developed to achieve differentiation and identification of microorganisms. Among these methods vibrational spectroscopic techniques (IR, Raman and SERS) are useful tools because of their rapidity and sensitivity. Recently we have shown that micro-Raman spectroscopy in combination with a support vector machine is an extremely ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
187
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(194 citation statements)
references
References 27 publications
3
187
1
3
Order By: Relevance
“…However structures like cellulose (polymerized glucose) lack these bands and instead has a strong peak at 1100 cm −1 and 2900 cm −1 with many broad and overlapping bands. [70,[115][116][117].…”
Section: Carbohydratesmentioning
confidence: 99%
“…However structures like cellulose (polymerized glucose) lack these bands and instead has a strong peak at 1100 cm −1 and 2900 cm −1 with many broad and overlapping bands. [70,[115][116][117].…”
Section: Carbohydratesmentioning
confidence: 99%
“…Due to the coherent nature of the CARS process, the resultant signal strength is boosted compared to linear confocal Raman microscopy and, hence, CARS microscopy enables fast image acquisition (Potma et al, 2001). However, in contrast to conventional Raman microspectroscopy (Baia et al, 2002;Rö sch et al, 2003;Harz et al, 2005), single-mode CARS microscopy yields images based on univariant results. Thereby, the information content to be obtained is limited to the spatial distribution of a single preselected Raman-active mode.…”
mentioning
confidence: 99%
“…Additionally, it can also be observed that S1 and S2 branch away from S3 and S4 indicating a clear separation between the pathogenic and non-pathogenic E. coli. The results that we obtained show that this measure of overall signal variance within a set of spectra obtained from different strains belonging to the same species can be as large as the interspecies signal variance 22 . Principal component analysis in the mean centred data, using NIPALS algorithm was performed on the Raman spectra obtained from the four strains of E.coli and the results are discussed in this section.…”
Section: Multivariate Analysismentioning
confidence: 74%
“…Moreover, aqueous samples can be easily studied as water is a weak Raman scatterer and enables monitoring of biological systems in live condition. Furthermore, the level of specificity can be enhanced by combining this technique with chemometric methods 21,22 as even the most subtle changes are expected to be picked up by this technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation